Bilan des études sur Théodore Agallianos : 1966-2011 - Blanchet, Marie-Héléne (The Gleaner, 2011)
A REPORT ON STUDIES ABOUT THEODORE AGALLIANOS (1966-2011) C. Patrineles devoted his doctoral thesis to Theodore Agallianos’ life and writings and also edited two of his speeches. In this still authoritative book, he listed all the manuscripts containing Agallianos’ works and all the existing editions. This article provides an update of this information in light of recent studies; it also catalogues the entire bibliography published about Agallianos since 1966. MARIE-HELENE BLANCHET